Layer-by-Layer Technique as a New Approach to Produce Nanostructured Films Containing Phospholipids as Transducers in Sensing Applications - Aoki, P. H. B. [UNESP]; Volpati, D. [UNESP]; Riul, A.; Caetano, Wilker [UNESP]; Constantino, C. J. L. [UNESP] (Amer Chemical Soc, 2009)
Phospholipids are widely used as mimetic systems to exploit interactions involving biological membranes and pharmacological drugs, In this work, the layer-by-layer (LbL) technique was used as a new approach to produce multilayered thin films containing biological phospholipids applied as transducers onto Pt interdigitated electrodes forming sensing units of an electronic tongue system. Low concentrations (nM level) of a phenothiazine compound were detected through impedance spectroscopy. Both negative 1,2-dipalmitoyl-sn-3-glycero-[phosphor-rac-(1-glycerol)] (DPPG) and zwitterionic i.-alpha-1,2-dipalmitoyl-sn-3-glycero-phosphatidylcholine (DPPC) phospholipids were used to produce the LbL films, whose molecular architecture was monitored combining spectroscopy and microscopy at micro and nanoscales. The sensor array was complemented by Langmuir-Blodgett (LB) monolayers of DPPG and DPPC deposited onto Pt interdigitated electrodes as well. It was found that the distinct molecular architecture presented by both LbL, and LB films plays a key role on the sensitivity of the sensor array with the importance of the LbL films being demonstrated by principal component analysis (PCA).